THE EFFECT OF PREPARATION CONDITIONS OF RAPIDLY SOLIDIFIED IRON BASED GRANULES ON PROPERTIES OF COMPOSITE MATERIAL FORMED BY CASTING TECHNOLOGY - A. S. Kalinichenko; V. A. Sheinert; V. A. Kalinichenko; A. G. Slutsky (Литьë и металлургия, 2017)
The variety of requirements for friction pairs requires the development of different technologies for the production of tribological materials with reference to the operation modes. Composite materials obtained by the casting technology have been successfully applied for the normalization of the thermomechanical state of the steam turbines. These composites consist of the matrix based on copper alloys reinforced with cast iron granules. Because the structure and properties of cast iron are determined by the conditions of their production studies have been conducted on determination of preparation conditions on grain structure and properties of the synthesized composite material. Using an upgraded unit for production of granules technological regimes were determined providing narrow fractional composition. It has been found that granules formed are characterized with typical microstructure of white cast iron containing perlite and ledeburite. Microhardness of pilot cast iron granules is characterized by high values (from 7450 up to 9450 MPa) and depends on the size of the fraction. Composite materials obtained using experimental granules had a microhardness of the reinforcing cast iron granules about 3500 MPa, and a bronze matrix – 1220 MPa, which is higher than the hardness of the composite material obtained by using the annealed DCL-1granules (2250 MPa). Metal base of experimental granules in the composite material has the structure of perlitic ductile iron with inclusions of ferrite not exceeding 10–15% and set around a flocculent graphite. As a result, the increase of physical-mechanical properties of finished products made of composite material is observed.